2011
DOI: 10.3109/17453674.2011.566136
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with surgically treated lumbar disc herniation

Abstract: Background and purpose Health-related quality of life (HRQoL) instruments have been of increasing interest for evaluation of medical treatments over the past 10–15 years. In this prospective, long-term follow-up study we investigated the influence of preoperative factors and the change in HRQoL over time after lumbar disc herniation surgery.Methods 117 patients surgically treated for lumbar disc herniation (L4-L5 or L5-S1) were evaluated with a self-completion HRQoL instrument (EQ-5D) preoperatively, after 2 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
3
16
1
1
Order By: Relevance
“…Studies conducted by many authors [6,12,14,15] showed that patients with a herniated disc in lumbo -sacral region experienced pain sensations of a medium intensity which was confirmed by own study. However, postoperative pain sensation is reduced [5,6,14,[16][17][18] as was also confirmed by this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Studies conducted by many authors [6,12,14,15] showed that patients with a herniated disc in lumbo -sacral region experienced pain sensations of a medium intensity which was confirmed by own study. However, postoperative pain sensation is reduced [5,6,14,[16][17][18] as was also confirmed by this study.…”
Section: Discussionsupporting
confidence: 82%
“…Studies conducted by other authors confirm the positive effect of surgery on the quality of life in patients who underwent surgery [3,[16][17][18]20]. In this study, the evaluation of functional condition of patients was made with the use of ODI.…”
Section: Discussionmentioning
confidence: 85%
“…The most common physical prognostic factor that was investigated in 5 studies [34-37, 39-41] was pre-operative duration of leg pain, followed by intensity of pre-operative leg pain investigated in 3 studies [36][37][38]41], and pre-operative back pain investigated in 2 studies [36,37,41].…”
Section: Physical Prognostic Factorsmentioning
confidence: 99%
“…Pre-operative duration of leg pain was included in 5 studies [34][35][36][37][38][39]41] as a candidate prognostic factor. There were inconsistencies regarding the association between the duration of pre-operative leg pain and numerous outcomes.…”
Section: Duration Leg Painmentioning
confidence: 99%
“…Consta de una escala analógica visual que abarca una puntuación de 0 a 100, siendo 0 el peor estado de salud y 100 el mejor estado, e incluye cinco dimensiones, que son movilidad, autocuidado, actividades de la vida diaria, dolor/malestar y ansiedad/depresión. Cada dimensión tiene tres posibles respuestas o niveles de problema que presentan en esa dimensión (ausencia que se codifica con 1, moderado que se codifica con 2 o grave que se codifica con 3) 24 . El niño debe marcar el nivel de problemas, dentro de cada dimensión, que mejor describa su estado de salud en ese día.…”
Section: Métodounclassified